US pediatric pulmonology workforce. Issue 4 (12th March 2019) - Harris, Christopher; Katkin, Julie; Cataletto, Mary; Dorkin, Henry; Laskosz, Laura; Ruch‐Ross, Holly
Abstract: Aim: Children with respiratory conditions benefit from care provided by pediatric pulmonologists. As these physicians are a small portion of the overall pediatric workforce, it is necessary to understand the practices and career plans of these specialists. Methods: An internet survey was developed by the American Academy of Pediatrics Division of Workforce and Medical Education Policy and sent to members of the American Academy of Pediatrics and American College of Chest Physicians who identified as pediatric pulmonary physicians. Results: Responses were received from 485 physicians and were compared to the results of a similar survey done in 1997. Of those completing the survey, 63% were male and 37% female, with increased number of females since the earlier poll. The average calculated age was 56 years. They worked 54 h per week, down from 59 h in the prior survey. Pediatric pulmonologists are overwhelmingly clinicians (92%) with major responsibilities for administration (79%), teaching (78%), and research. Basic science research was rarely reported (7%). Pediatric pulmonologists felt that referrals had become more complicated in the recent past. Nearly all planned to maintain Pediatric Pulmonology Sub‐board certification, though one third planned to cut back on clinical workload in the next decade. Many were concerned that the number needed in the profession in a decade would be inadequate with significant concerns about funding for those positions. Conclusion: Overall, these results reflect the current state of the workforce and the need to monitor the supply of practitioners in the future.